Activation of 6-bromoquinoline by nitration: synthesis of morpholinyl and piperazinyl quinolines - Cakmak, Osman; Okten, Salih; Alimli, Dilek; Saddiqa, Aisha; Ersanli, Cem Cuneyt (ARKAT USA INC, 2018)
Quinoline forms the key skeletal component of a number of important natural products and pharmacologically-active compounds. Despite a tremendous amount of research pertaining to the derivatization of quinoline, very few general synthetic routes are described in the literature starting from quinoline or tetrahydroquinoline. A simple and convenient method for the polyfunctionalization of quinolines via nitration of bromoquinolines has been developed. This method represents a new synthetic approach to convert brominated nitroquinoline derivatives into useful cyclic amines via nucleophilic-substitution (SNAr) reaction. [GRAPHICS] .
Keywords: Nitration; N-oxidation; 6-bromoquinoline; aminoquinoline; quinoline N-oxides; morpholinyl and piperazinyl quinolines; REGIOSELECTIVE BROMINATION; ANTICANCER ACTIVITIES; DERIVATIVES; AGENTS; Chemistry